Mass-loss rates from decomposition of plant residues in spruce forests near the northern tree line subject to strong air pollution - Lukina, Natalia V.; Orlova, Maria A.; Steinnes, Eiliv; Artemkina, Natalia A.; Gorbacheva, Tamara T.; Smirnov, Vadim E.; Belova, Elena A. (Environmental science and pollution research international, 2017)
Mass-loss rates during the early phase of decomposition of plant residues were studied for a period of 3 years in Norway spruce forests subjected to air pollution by Cu-Ni smelters on the Kola Peninsula, northwest Russia. Litterbags were deployed in two main patches of forests at the northern tree line, between and below the crowns of spruce trees older than 100 years. The study results demonstrated the dependence of the decomposition rates on the initial concentrations of nutrients and the C/N and lignin/N ratios in plant residues. Lower rates of mass loss in forests subject to air pollution may be related to low quality of plant residues, i.e. high concentrations of heavy metals, low concentrations of nutrients, and high lignin/N and C/N ratios. The increased losses of Ca, Mg, K, and Mn from plant residues in these forests compared to the reference were, probably, related to leaching of their compounds from the residues. The relatively high rates of heavy metal accumulation in the residues were most likely related to uptake of pollutants from the atmosphere, as well as to the lower mass-loss rates. The present study results demonstrate that the forest patchiness should be taken into account in assessment and predictions of decomposition rates in Norway spruce forests. Mass-loss rates of plant residues below the crowns of old spruce trees were significantly lower than those in the patches between the crowns. This was explained by the high C/N and lignin/N ratios in the residues of evergreens which contribute significantly to litterfall below the crowns and by lower soil temperature during winter and spring below the crowns. In addition, a lower amount of precipitation reaching the forest floor below the dense, long crowns of old Norway spruce trees may result in considerably lower washing out of the organic compounds from the residues. Lower mass-loss rates below the crowns of old spruce trees may be part of the evidence that the old-growth spruce forests can continue to accumulate carbon in soil.